Landmark-based morphometric and meristic variations of Glossogobius giuris in three stocks (Journal of the Bangladesh Agricultural University, 2013)
Landmark-based morphometric and meristic analysis of pond, haor and estuary populations of Glossogobius giuris (Hamilton,1822) (Perciformes:Gobiidae) were done to find out variations among the three stocks. Samples were collected from three different regions such as pond of Mymensingh, haor of Kishoreganj and estuary of Barisal. Significant differences (*P